Myakka bug, Ischnodemus variegatus (Signoret) (Insecta: Hemiptera: Blissidae) - Cecil O. Montemayor; Rodrigo Diaz; William A. Overholt; Amanda Hodges (EDIS)
EENY471, a 6-page illustrated fact sheet by Cecil O. Montemayor, Rodrigo Diaz, William A. Overholt, and Amanda Hodges, is part of the Featured Creatures collection. It describes this newly introduced exotic insect species hosted by the invasive West Indian marsh grass, Hymenachne amplexicaulis — synonymy, description, life cycle and biology, damage, economic importance, and natural enemies. Includes references. Published by the UF Department of Entomology and Nematology, February 2010.